When Fashion is Fleeting: Transitory Collective Beliefs and the Dynamics of TQM Consulting - David, Robert J.; Strang, David (Academy of Management Journal, 2006)
We analyze changes over time in the types of consulting firms offering total quality management services. When TQM was a booming management fashion, consultants tended to be generalists with weak links to the technical foundations of the practice; after the fashion went bust, TQM consulting was increasingly populated by specialists with quality control expertise. These results suggest that fashionable practices can return to their technical roots after the hype is over, reversing the usual institutional trajectory. They also help explain why fashion booms are so fragile and how management practices can be sustained once a boom is over.